THE AGRARIAN CONFLICTS IN CASTILLA DURING THE EIGHTEENTH CENTURY. THE EXAMPLE OF THE MANCHA ORIENTAL - Cózar Gutiérrez, Ramón (Revista de Historia Social y de las Mentalidades, 2011)
For a long time the historiography has  represented the eighteenth-century Spain  as an idyllic paradise where concord and  unimportant facts prevailed. Far from being  true, the situation lived in Spain was marked  by a social conflict that can not be ignored.  In this article we want to reinforce this idea,  noting all the conflicting facts that occurred  in La Mancha of Albacete in the years 1765,  following the promulgation of the Royal  Pragmatic liberalization of trade in grains,  and 1766, where the climate of tension  between generally favored by the mutiny in  Madrid, two provincial riots that occupy an  important place in Spanish history: Tobarra  and Liétor. The first, being the first case  of rebellion after the 1766 riot in Madrid,  while the second has been considered by  some authors as a representative of the  finest examples of nineteenth century social  unrest. We hope this study can contribute in  some way to a better understanding of the  social conflict in eighteenth-century Spain  in general and in particular La Mancha  Oriental.
Keywords: social conflicts; riots; Mancha Oriental; 18th century